"Every Novel is a New Country": A Conversation with Junot Díaz. Issue 3 (26th May 2020) - Sun, Lu
ABSTRACT: Junot Díaz (born on December 31, 1968) is a Dominican-American writer, creative writing professor at the Massachusetts Institute of Technology, and fiction editor at Boston Review . He was born in Santo Domingo, Dominican Republic, and immigrated with his family to New Jersey when he was six years old. He earned a Bachelor of Arts degree from Rutgers University, and obtained his MFA from Cornell University. Díaz is the author of the critically acclaimed short story collection Drown (1996), The Brief Wondrous Life of Oscar Wao (2007), which won the 2008 Pulitzer Prize for Fiction and the National Book Critics Circle Award, and This Is How You Lose Her (2012), a New York Times bestseller and National Book Award finalist. He received a MacArthur "Genius" Fellowship in 2012, and was also the recipient of PEN/Malamud Award, Dayton Literary Peace Prize, Guggenheim Fellowship, and PEN/O Henry Award. He was appointed chair of the Pulitzer Board in April 2018. This conversation took place at MIT, Cambridge, Massachusetts, on September 6, 2019.